Participatory Monitoring and Evaluation on Sustainability of Potato Projects in Rubanda District, Uganda - Turyasingura, John Bosco; Byarugaba, Arinaitwe Julius; Moses, Agaba; Alice, Ngele Mwazuna; Atukwase, Jasper (International Journal of Management and Business Applied, 2026)
Examining how participatory monitoring and evaluation affects the sustainability of potato projects in Rubanda District was the goal of this study. The unavailability of potato projects in Rubanda District served as the basis for this investigation. The survey design used in this study was cross-sectional. A total of 139 respondents' data was gathered, and both quantitative and qualitative analysis were performed. Frequency tables were utilized to display the data because descriptive analysis involved describing a single variable and its characteristics. A Pearson correlation matrix was used at the bivariate level to determine the connections between the dependent and predictor variables. To fit the data, a linear regression model was employed. Monitoring and evaluation in potato projects have a positive impact on project sustainability, according to research findings from the regression model (R=756). The primary finding of this study is that the sustainability of potato projects in the Rubanda district is impacted by monitoring and evaluation. Therefore, the study suggests that in order to ensure the sustainability of potato projects in the Rubanda district, project managers should give careful thought to project monitoring and evaluation.